Comparing Two Worldview Manifestos: Abraham Kuyper's Six Stone Lectures and Kadir Mısıroğlu's Islamic Worldview. - Topcan, Özlem (Journal of Ecumenical Studies)
This essay examines how Abraham Kuyper (1837–1920), Dutch Neo-Calvinist theologian and statesperson, and Kadir Mısıroğlu (1933–2019), Turkish Islamic apologist and polemicist, deployed the concept of "worldview" as a framework for resisting secular modernity. Rather than a set of doctrines, both presented "worldview" as a comprehensive system ordering knowledge, society, and politics. Through comparative textual analysis of Kuyper's Stone Lectures (1898) and Mısıroğlu's 2000 study, İslam Dünya Görüşü (Islamic Worldview), which shows that, while both rejected the neutrality of reason, Kuyper channeled this stance into pluralist institutional reform, whereas Mısıroğlu advanced revelatory absolutism and called for civilizational rupture. Kuyper's model emphasizes confessional scholarship, sphere sovereignty, and pillarization; Mısıroğlu's insists on tawhid as the sole epistemic axiom and the restoration of Sharia as public law. The findings highlight two contrasting modalities of religious response to modernity: reformist continuity and revolutionary replacement. The essay contributes to political theology and comparative religion by offering a typology of these modalities and reassessing secularism's claim to universal legitimacy.